Exogenous salicylic acid and thiourea ameliorate salt stress in wheat by enhancing photosynthetic attributes and antioxidant defense - Farzana, Sumaiya; Rasel, Md.; Tahjib-Ul-Arif, Md.; Galib, Md. Asadulla Al; Sarker, Kishor Kumar; Hossain, Mohammad Afzal (Journal of the Bangladesh Agricultural University, 2020)
Salinity stress is a worldwide problem, constraining global crop production seriously. Recent global climate change has made this situation more serious. Exogenous application of potential protectants such as salicylic acid (SA) and thiourea (TU) can be an important approach to alleviate the adverse effects of salinity stress on plants. Therefore, a hydroponic experiment was conducted to investigate the ameliorating effect of SA and TU on salt stress in a wheat genotype namely BARI Gom-30 considering the growth traits, photosynthetic parameters and antioxidant enzyme activities. The experiment was laid out by following randomized complete block design (RCBD) with three replications and five treatments viz., control, salt, salt + SA, salt + TU, and salt + SA + TU. Salinity stress caused significant reduction of different growth traits such as plant height, shoot and root length, fresh weight and dry weight of root and shoot in wheat genotype. The leaf water status, different photosynthetic parameters and intracellular proline contents were severely shortened in the leaves of salt stressed plants. However, exogenous application of SA or TU on salt stressed wheat plants showed a significant increase in growth traits by up regulating the levels of chlorophyll content, photosynthetic pigments and proline contents in comparison to salt treated plants alone. The higher Na+/K+ was noted in the leaves of stressed seedlings and therefore, the wheat plants suffered more oxidative damage due to the higher production of H2O2 and MDA under salinity stress. Besides these, the activities of antioxidant enzymes namely CAT, POD and APX were slightly enhanced due to the imposition of salt on wheat seedlings compared to control treated plants. In contrast, SA or TU mediated ameliorating effect of salt stress maintained the lower Na+/K+ as well as the minimum production of H2O2 and MDA in BARI Gom-30. This is might be due to the higher increment of CAT, POD and APX enzyme activities in the stressed wheat genotypes supplemented with SA or TU reflecting the positive role of SA or TU against salt-induced oxidative stress in BARI Gom-30. Individual foliar application of SA and TU was found to be more effective in improving salt stress tolerance in BARI Gom-30 than that of the combined application of SA and TU. J Bangladesh Agril Univ 18(2): 272–282, 2020 https://doi.org/10.5455/JBAU.86574